Global Monetary Tightening : Emerging Markets Debt Dynamics and Fiscal Crises - Escolano, Julio (IMF Working Papers; Working Paper, 2014)
This paper finds that tightening global financial conditions can worsen emerging economies' public debt dynamics through an increasing interest rate-growth differential, particularly if coupled with high global risk aversion. Latin America and emerging Europe are the regions most likely to be adversely affected. In addition, historical evidence-analyzed by means of a Poisson count model-suggests that the frequency of sovereign debt crises increases in emerging economies at the early stage of U.S. monetary tightening cycles, at times in which the term spread also rises. The timing may be related to abrupt switches of expectations about the future course of policy in the early stages of tightening cycles.